PHYSICOCHEMICAL PROPERTIES AND PHARMACOLOGY OFAMLODIPINE BESYLATE A BRIEF REVIEW - Syed Furqan Ahsan et al (Baqai Journal of Health Sciences)
Hypertension is one of the well-studied risk factors for cardiovascular diseases and the oldest class of hypertensive drugsisthe calcium channel blockers.Amlodipine besylate (ADB) belongsto the dihydropyridine family and is known as an effective initial treatment for hypertension and angina. It has a gradual onset of action and is administered in concomitant diseases with minimal side effects. Its basic mechanism of action is the blockage of calcium ions influx into cardiac muscles and vascular muscles. The physical appearance of ADB is white crystalline with a molecular weight of 567.1. Its 6.9 mg is equivalent to 5 mg of amlodipine (AM) free base. This review focuses on all the basic aspects of ADB which is one of the initial treatment regimens for cardiovascular diseases since last two decades